A colour opponent model that explains tsetse fly attraction to visual baits and can be used to investigate more efficacious bait materials. - Roger D Santer (Public Library of Science (PLoS), 2014)
Palpalis group tsetse flies are the major vectors of human African trypanosomiasis, and visually-attractive targets and traps are important tools for their control. Considerable efforts are underway to optimise these visual baits, and one factor that has been investigated is coloration. Analyses of the link between visual bait coloration and tsetse fly catches have used methods which poorly replicate sensory processing in the fly visual system, but doing so would allow the visual information driving tsetse attraction to these baits to be more fully understood, and the reflectance spectra of candidate visual baits to be more completely analysed. Following methods well established for other species, I reanalyse the numbers of tsetse flies caught at visual baits based upon the calculated photoreceptor excitations elicited by those baits. I do this for large sets of previously published data for Glossina fuscipes fuscipes (Lindh et al. (2012). PLoS Negl Trop Dis 6: e1661), G. palpalis palpalis (Green (1988). Bull Ent Res 78: 591), and G. pallidipes (Green and Flint (1986). Bull Ent Res 76: 409). Tsetse attraction to visual baits in these studies can be explained by a colour opponent mechanism to which the UV-blue photoreceptor R7y contributes positively, and both the green-yellow photoreceptor R8y, and the low-wavelength UV photoreceptor R7p, contribute negatively. A tool for calculating fly photoreceptor excitations is made available with this paper, and this will facilitate a complete and biologically authentic description of visual bait reflectance spectra that can be employed in the search for more efficacious visual baits, or the analysis of future studies of tsetse fly attraction.